Developing predictive model for the critical properties of fuels containing esters based on the experimental study of methyl butanoate + alcohols + n-alkanes mixtures. (15th October 2020) - Wang, Chengjie; Lan, Tian; Liu, Xiangyang; Zhang, Ying; He, Maogang
Graphical abstract: Highlights: T c and p c for mixtures containing methyl butanoate are first reported. Trends of critical curves are described and the nonlinearly of curves is analyzed. Critical property data agree well with correlated results by different models. HWCL model is developed to applied to the fuel blends containing esters. Abstract: Critical properties which are the basis for the calculation of other thermophysical properties, are required to evaluate the fuel performance during the process of fuel design. A predictive model, which does not require critical temperature ( T c ) and critical pressure ( p c ) of each component, is further developed for T c and p c for the fuel blends containing esters based on the new measured data for the mixtures of biodiesel surrogate methyl butanoate, alcohols and n-alkanes (methyl butanoate + n-alkanes (C = 6, 7, 8), methyl butanoate + n-alcohols (C = 3, 4), methyl butanoate + n-hexane + n-propanol). The accuracy of this modified model is proved by the comparison with Li model, Chueh–Prausnitz model and He–Liu model. All the critical curves of the mixtures experimentally studied in this work show good linearity except the mixture of methyl butanoate + n-alkanes due to different characteristics between two components. The performances of Redlich–Kister model, PR–WS model, Cibulka model and Singh–Sharma model in correlating the measured data are also verified.